Geographers of the ancient Greek world : selected texts in translation. - Shipley, Graham, 1956- (Cambridge University Press, 2024)
Ancient Greek geographical writing is represented not just by the surviving works of the well-known authors Strabo, Pausanias, and Ptolemy, but also by many other texts dating from the Archaic to the Late Antique period. Most of these texts are, however, hard for non-specialists to find, and many have never been translated into English. This volume, the work of an international team of experts, presents the most important thirty-six texts in new, accurate translations. In addition, there are explanatory notes and authoritative introductions to each text, which offer a new understanding of the individual writings and demonstrate their importance: no longer marginal, but in the mainstream of Greek literature and science. The book includes twenty-eight newly drawn maps, images of the medieval manuscripts in which most of these works survive, and a full Introduction providing a comprehensive survey of the field of Greek and Roman geography